Apoptosis mechanisms induced by 15d-PMJ2 in HCT116 colon cancer cells: insights into CHOP10/TRB3/Akt signaling - Albassam, Hussam; Ladin, Daniel A.; Elhassanny, Ahmed; Burns, Colin; Van Dross-Anderson, Rukiyah (Frontiers in Pharmacology, 2023)
Agents that stimulate the endoplasmic reticulum (ER) stress pathway are being exploited pharmacologically to induce cancer cell death. Cytotoxic ER stress is typically regulated by the transcription factor, C/EBP homologous protein 10 (CHOP10). Products of CHOP10 transcription include the pro-apoptotic proteins: ER oxidoreductase 1α (ERO1α), death receptor-5 (DR5), and tribbles-related protein 3 (TRB3). Our previous findings showed cell death induced by 15-deoxy-Δ12,14 prostamide J2 (15d-PMJ2) occurred in an ER stress-dependent manner. However, the pathway by which 15d-PMJ2 regulates ER stress-mediated death downstream of CHOP10 has not been identified. Our results demonstrate 5 µM 15d-PMJ2 increased CHOP10 expression and apoptosis in HCT116 colon cancer cells. In cells treated with pharmacological inhibitors of ER stress, 15d-PMJ2-induced apoptosis was reliant upon the ER stress pathway. To investigate the role of CHOP10 and its transcriptional products in apoptosis, genetic deletion of CHOP10 (CHOP10-KO) was performed using the CRISPR/Cas9 system. The apoptotic action of 15d-PMJ2 was blunted in cells lacking CHOP10 expression. The deletion of CHOP10 reduced the expression of DR5, ERO1α, and TRB3 although only the expression of TRB3 was significantly reduced.Therefore, we overexpressed TRB3 in CHOP10-KO cells and observed that the activation of Akt was inhibited and 15d-PMJ2-induced apoptosis was restored. Thus, a mechanism of apoptosis elicited by 15d-PMJ2 includes the stimulation of CHOP10/TRB3/Akt inhibition. Given the important role these signaling molecules play in cancer cell fate, 15d-PMJ2 may be an effective inducer of apoptosis in cancer cells.